2021
DOI: 10.3390/jcm10214873
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Fluid Balance on Long-Term Mortality in Critically Ill Surgical Patients: A Retrospective Cohort Study in Central Taiwan

Abstract: Fluid balance is an essential issue in critical care; however, the impact of early fluid balance on the long-term mortality in critically ill surgical patients remains unknown. This study aimed to address the impact of day 1–3 and day 4–7 fluid balance on the long-term mortality in critically ill surgical patients. We enrolled patients who were admitted to surgical intensive care units (ICUs) during 2015–2019 at a tertiary hospital in central Taiwan and retrieved date-of-death from the Taiwanese nationwide dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Given that patients in ICU often received mechanical ventilation, experienced fear were deprived of normal sleep, felt isolation; therefore, appropriate sedation, at least light sedation, is recommended as a standard of care in critically ill patients and hence leads to difficulties to identify pain based on facial expressions ( 32 ). In addition to the impact of sedation on pain assessment, subtle facial muscle movements might also be confounded by facial oedema resulting from fluid overload, which is highly prevalent in critically ill patients who underwent fluid resuscitation, as we have shown in our previous studies ( 33 , 34 ). Collectively, automated pain assessment based on facial expressions in critically ill patients is currently an unmet need in the research field of medical AI due to the aforementioned difficulties.…”
Section: Discussionmentioning
confidence: 82%
“…Given that patients in ICU often received mechanical ventilation, experienced fear were deprived of normal sleep, felt isolation; therefore, appropriate sedation, at least light sedation, is recommended as a standard of care in critically ill patients and hence leads to difficulties to identify pain based on facial expressions ( 32 ). In addition to the impact of sedation on pain assessment, subtle facial muscle movements might also be confounded by facial oedema resulting from fluid overload, which is highly prevalent in critically ill patients who underwent fluid resuscitation, as we have shown in our previous studies ( 33 , 34 ). Collectively, automated pain assessment based on facial expressions in critically ill patients is currently an unmet need in the research field of medical AI due to the aforementioned difficulties.…”
Section: Discussionmentioning
confidence: 82%
“…e TCVGH critical care data warehouse was used to retrieve data with respects to demographic data, Charlson comorbidity index (CCI), Acute Physiology and Chronic Health Evaluation (APACHE) II score, presence of shock, receiving mechanical ventilation, underwent renal replacement, management including blood transfusion, and laboratory data [10]. Previous studies, including our studies, have shown the mortality association of early (day 1-3) overall fluid balance status and culture positivity of microbial culture during ICU admission, we hence included these two variables as covariates in the present study [11][12][13].…”
Section: Covariatesmentioning
confidence: 99%